Enhancing Students’ Oral Production by Using Drama Activities (2022)
ABSTRACT : The aim of this action-research was to enhance students’ oral production by using drama activities. It was developed in a rural public school in the municipality of El Carmen de Viboral with 38 graders. The Genre-Based Approach (GBA) guided the action strategies of this study, including three stages: modeling, joint construction, and independent construction. Data was collected through informal talks, focus groups, tests, and personal journals. Findings showed the usefulness of drama activities to improve students’ oral production, having direct positive impacts on their performance, integrating students’ interests, being an encouraging methodology for students, and allowing to use a wide range of teaching strategies. Moreover, problems regarding extracurricular activities, lack of time, disposition, basic knowledges, and confidence were found.